Investigation of Responsiveness to Thyrotropin-Releasing Hormone in Growth Hormone-Producing Pituitary Adenomas. (21st November 2013) - Chin, Sang Ouk; Rhee, Sang Youl; Chon, Suk; Hwang, You-Cheol; Jeong, In-Kyung; Oh, Seungjoon; Kim, Sung-Woon
Abstract : Objective . The aim of this study was to investigate how the paradoxical response of GH secretion to TRH changes according to tumor volumes. Methods . Patients with newly diagnosed acromegaly were classified as either TRH responders or nonresponders according to the results of a TRH stimulation test (TST), and their clinical characteristics were compared according to responsiveness to TRH and tumor volumes. Results . A total of 41 acromegalic patients who underwent the TST were included in this study. Between TRH responders and nonresponders, basal GH, IGF-I levels, peak GH levels, and tumor volume were not significantly different, but the between-group difference of GH levels remained near significant over the entire TST time. Δ GH max-min during the TST were significantly different according to the responsiveness to TRH. Peak GH levels and Δ GH max-min during the TST showed significantly positive correlations with tumor volume with higher levels in macroadenomas than in microadenomas. GH levels over the entire TST time also remained significantly higher in macroadenomas than in microadenomas. Conclusion . Our data demonstrated that the paradoxical response of GH secretion to TRH in GH-producing pituitary adenomas was not inversely correlated with tumor volumes.